Agronomic experimentation on-station for research platforms in Mexico: Management Guide - CGIAR Research Program on Wheat (2021)
a method for agronomic research platforms that has been applied by partners in more than 50 locations in Mexico. See also https://doi.org/10.1080/14778238.2021.1884010 https://doi.org/10.1080/14735903.2021.1945853